Tofu Wastewater (TWW) Treatment and Hydrogen (H2) Production by Using A Microbial Electrolysis Cell (MEC) System - Satar, Ibdal; Sirajuddin, Muhammad Mar’ie; Permadi, Adi; Latifatunnajib, Sukma (Indonesian Journal of Environmental Management and Sustainability, 2023)
High organic pollutant in tofu wastewater (TWW) raises a negative impact on environmental sustainability and health. Therefore, the TWW must be treated before it is discharged into the environment. Microbial electrolysis cell (MEC) is one of the green technologies that can be used to treat wastewater and generate hydrogen as well. This work tries to investigate the performance of MEC based on the decrement of organic pollutants in TWW. Some important parameters of organic pollutants in TWW such as chemical oxygen demand (COD), biological oxygen demand (BOD), total suspended solids (TSS), total dissolved solids (TDS), total solid (TS), and pH were evaluated before and after MEC operation. The results showed that the COD and BOD levels decreased around 56% and 35% while pH increased from 7.90 to 7.16. Additionally, the TSS, TDS, and TS decreased by around 35.0%, 45.5%, and 33.2%. In addition, the optimum hydrogen yield (YH2) and hydrogen production rate (QH2) were obtained at 114 ± 0.1 mL H2/g COD 360 ± 20 mL H2/L/d. Overall, the MEC system could be used to reduce the level of organic pollutants in TWW and generated H2 at the same time.